2018
DOI: 10.5483/bmbrep.2018.51.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and migration mechanism of caffeoylserotonin and serotonin via serotonin 2B receptor in human keratinocyte HaCaT cells

Abstract: Caffeoylserotonin (CaS), one derivative of serotonin (5-HT), is a secondary metabolite produced in pepper fruits with strong antioxidant activities. In this study, we investigated the effect of CaS on proliferation and migration of human keratinocyte HaCaT cells compared to that of 5-HT. CaS enhanced keratinocyte proliferation even under serum deficient condition. This effect of CaS was mediated by serotonin 2B receptor (5-HT2BR) related to the cell proliferation effect of 5-HT. We also confirmed that both CaS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…During skin wound healing, the migration and proliferation of keratinocytes can be mediated by various signaling pathways. Previous reports show that Akt signal activation participates in the regulations of various cellular events, such as cell survival, growth, proliferation, and migration [26,33] and that the Akt pathway is involved in the migration and proliferation of keratinocytes [5,24,34] . In the present study, we found that SCF absolute at concentrations of 100 and 150 μg/mL increased Akt phosphorylation in HaCaT cells, thus indicating, that it stimulated migration and proliferation via Akt activation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…During skin wound healing, the migration and proliferation of keratinocytes can be mediated by various signaling pathways. Previous reports show that Akt signal activation participates in the regulations of various cellular events, such as cell survival, growth, proliferation, and migration [26,33] and that the Akt pathway is involved in the migration and proliferation of keratinocytes [5,24,34] . In the present study, we found that SCF absolute at concentrations of 100 and 150 μg/mL increased Akt phosphorylation in HaCaT cells, thus indicating, that it stimulated migration and proliferation via Akt activation.…”
Section: Discussionsupporting
confidence: 72%
“…The MAPK family is conventionally divided into three subgroups, namely, Erk1/2, c‐Jun NH2‐terminal kinase (JNK), and p38 MAPK [35] . It has been shown downregulation of the Erk1/2 signal reduces keratinocyte migration and proliferation, [36,37] and that increased Erk1/2 phosphorylation is positively associated with keratinocyte migration and proliferation [24,34] . p38 MAPK phosphorylation has also been reported to mediate keratinocyte proliferation and migration [25,38] .…”
Section: Discussionmentioning
confidence: 99%
“…In accord, activation of HTR4 increased cell proliferation in intestinal crypts and promoted cell migration while reducing oxidative stress and apoptosis in Caco2 cells [127]. Similar effects on cell proliferation have been described in a keratinocyte HaCaT cell line, hepatic stellate cells, and pulmonary arterial smooth muscle cells [139][140][141]. These findings suggest that HTR activation could augment disease characterized by mucosal damage like IBD through stimulation of epithelial cell proliferation and hence mucosal healing.…”
Section: Neuronal Effects Of 5-ht On Gut Motility Enteric Neurogenesis and Maturation And Wound Healingsupporting
confidence: 68%
“…Cyclins are a family of proteins that regulate cell cycle progression by activating cyclin-dependent kinases (CDKs) [ 37 ]. Given the significance of the cyclin pathway in wound healing, the effects of IK on the regulation of cyclin families, especially cyclin D1 regulated by the MAPK/ERK pathway, should be investigated [ 38 , 39 ]. These results suggested that IK stimulates the MAPK/ERK pathway in keratinocytes, which is crucial in wound healing processes.…”
Section: Discussionmentioning
confidence: 99%